THE HISTORY OF ECONOMIC DEVELOPMENT OF THE REPUBLIC OF UZBEKISTAN AND THE REPUBLIC OF KAZAKHSTAN - Shukurov Sobir (Western European Studies, 2025)
This article examines the economic cooperation between Uzbekistan and Kazakhstan, one of Uzbekistan's major partners in Central Asia, from independence to the present, as well as the main directions and prospects. Strengthening regional integration, developing trade and economic ties, and issues of cooperation in the fields of energy and transport are at the center of the discussion. Security between the two countries, as well as the deepening of economic relations, efforts, and strategic significance, will be highlighted on a scientific-theoretical basis for future economic directions.
Keywords: Uzbekistan; Kazakhstan; economic ties